Pengaruh Pemberian Ekstrak Etanol 70% Stroberi (Fragaria X Annanassa Duchesne) Terhadap Kerusakan Morfologi Hepar Mencit (Mus Musculus) Yang Diinduksi Parasetamol Dosis Toksik - Widianto, Septian, Dr. Devi Usdiana Rosyidah, M.Sc (2017)
Strawberries (Fragaria x annanassa Duchesne) contains a wide variety of antioxidants, namely: flavonoids, ellagic acid, anthocyanins and vitamin C. Antioxidants are thought to have the effect to protect the liver from damage caused by oxidative stress. For this study to determine the effect of 70% ethanol extract of strawberry (Fragaria x annnanassa) in reducing core histological damage due pe mice hepatocyte mberian paracetamol. This research is an experimental laboratory methods With Post Test Only Control Group Design. Test animals used were 30 male mice (Mus musculus) strain male Swiss Webster 2-3 months old weighing 20-30 grams were divided into 5 groups: control group was given distilled Positive, Negative Control group was given 5.07 mg paracetamol / 20 grBB, treatment Group I (0.5 mg / 20 grBB mice), treatment Group II (1.0 mg / 20 grBB), and Group III treatment (2.0 mg / 20 grBB). Damage to liver cells was measured by counting the number of damaged cells that focuses on necrosis. Data were analyzed with the Kruskal-Wallis and Mann Whitney Post Hoc test. 70% ethanol extract of strawberry (Fragaria x annanassa Duchesne) dose of 0.5 mg / grBB, 1.0 mg / grBB, and 2.0 mg / grBB proven already provide a protective effect on liver cells of mice morphological damage due to toxic doses of paracetamol.